A Prospective Randomized Controlled Trial of Nonpharmacological Pain Management During Intravenous Cannulation in a Pediatric Emergency Department. Issue 7 (July 2016) - Miller, Kate; Tan, Xianghong; Hobson, Andrew Dillon; Khan, Asaduzzaman; Ziviani, Jenny; O'Brien, Eavan; Barua, Kim; McBride, Craig A.; Kimble, Roy M.
Abstract : Objectives: Intravenous (IV) cannulation is commonly performed in pediatric emergency departments (EDs). The busy ED environment is often not conducive to conventional nonpharmacological pain management. This study assessed the use of Ditto (Diversionary Therapy Technologies, Brisbane, Australia), a handheld electronic device which provides procedural preparation and distraction, as a means of managing pain and distress during IV cannulation performed in the pediatric ED. Methods: A randomized controlled trial with 98 participants, aged 3 to 12 years, was conducted in a pediatric ED. Participants were recruited and randomized into 5 intervention groups as follows: (1) Standard Distraction, (2) PlayStation Portable Distraction, (3) Ditto Distraction, (4) Ditto Procedural Preparation, and (5) Ditto Preparation and Distraction. Children's pain and distress levels were assessed via self-reports and observational reports by caregivers and nursing staff across the following 3 time points: (1) before, (2) during, and (3) after IV cannulation. Results: Caregivers and nursing staff reported significantly reduced pain and distress levels in children accessing the combined preparation and distraction Ditto protocol, as compared to standard distraction ( P ⩽ 0.01). This intervention also saw the greatest reduction in pain and distress as reported by the child. Conclusions: Caregiver reports indicate that using the combined Ditto protocol was most effective in reducing children's pain experiences while undergoing IV cannulation in the ED. The use of Ditto offers a promising opportunity to negotiate barriers to the provision of nonpharmacological approaches encountered in the busy ED environment, and provide nonpharmacological pain-management interventions in pediatric EDs.